Monitoring the occurrence of functional changes and disorders of the postural system in active basketball and football players - Kozel, M.; Nechvátal, P.; Gajdoš, M.; Cuj, J. (Zdravotnícke listy, 2020)
Background: The current high performance sport has reached the stage where it is important to achieve maximum performance, even at the cost that the athlete's physical load is exaggerated and often less than compensated by the activity that would eliminate the adverse effects of training or sports performance. Ultimately, this will be reflected in the quality of locomotor system, resp. posture. Objective: The aim of this work is to find out what is the occurrence of shortened muscles, monitor posture, movement stereotypes and diagnose the curvature of spine and mobility of individual segments in the sagittal plane of top athletes and compare these parameters with the group of athletes who play football and basketball. Materials and Methods: In our research participated top athletes (n = 60 men, 20 ± 2.9) of whom are 30 footballers and 30 are basketball players active for at least five years. To accomplish the research objectives, we used a shortened muscle test and a Janda motion stereotype, a postural test and a Spinal Mouse diagnostic device. The obtained results have been statistically processed. Conclusion: Among the active football and basketball players, we observed statistically significant differences (p<0.05) in the monitored parameters (shortened muscles, kyphosis, movement stereotypes, segmental mobility). For active basketball players, shortened muscles, increased kyphosis, worse motion stereotypes, worse segmental mobility and spinal curvature in the Th region are more common. In football players, these are especially shortened knee flexors and posture disorders in the pelvis and trunk.